The effect of need-oriented educational intervention on the general health of the elderly - Zahra Zandiyeh; Elaheh Zare; Tayebeh Mehrabi; Mansour Shiri (Wolters Kluwer Medknow Publications, 2017)
Introduction: Improving the health of the elderly must be based on their special needs that can be achieved through self-needs assessments through education, which is one of the most important tools in the field of health improvement. The aim of the present study was to evaluate the effect of need-oriented educational interventions on the general health of the elderly living in nursing homes. Materials and Methods: The present study is a clinical trial conducted among the elderly living at the Sadeghieh nursing home of Isfahan, Iran. Seventy elderly people who satisfied the inclusion criteria were selected and divided into two groups of case and control. The case group went through 8 sessions of group therapy for educating participants who were previously investigated through needs assessment. The control group received the usual health care. The general health level of the participants was evaluated before and 1 week and 1 month after the intervention using Goldberg's general health questionnaire. Data were analyzed using Chi-square test, independent t-test, paired t-test, Mann-Whitney test, and variance analysis. Results: The score of general health had no significant difference between both the groups before the intervention, however, the difference in the score between both the groups 1 week and 1 month after the intervention was significant (1 week after the intervention, the scores were 15.6 and 30.3, and 1 month after the intervention, the scores were 16 and 32.2, respectively) (P < 0.001). Conclusions: Need-oriented educational intervention is an effective, safe, and inexpensive method for improving the general health of the elderly living in nursing homes.